Gut microbial DNA and immune checkpoint gene Vsig4/CRIg are key antagonistic players in healthy aging and age-associated development of hypertension and diabetes - Liu, Matthew A.; Shahabi, Shandy; Jati, Suborno; Tang, Kechun; Gao, Hong; Jin, Zhongmou; Miller, Wyatt; Meunier, Frédéric A.; Ying, Wei; Bogaart, Geert van den; Ghosh, Gourisankar; Mahata, Sushil K. (Frontiers in Endocrinology, 2022)
ABSTRACT Aims: Aging is associated with the development of insulin resistance and hypertension which may stem from inflammation induced by accumulation of toxic bacterial DNA crossing the gut barrier. The aim of this study was to identify factors counter-regulating these processes. Taking advantage of the Chromogranin A (CgA) knockout (CgA-KO) mouse as a model for healthy aging, we have identified Vsig4 (V-set and immunoglobulin domain containing 4) as the critical checkpoint gene in offsetting age-associated hypertension and diabetes. Methods and Results: The CgA-KO mice display two opposite aging phenotypes: hypertension but heightened insulin sensitivity at young age, whereas the blood pressure normalizes at older age and insulin sensitivity further improves. In comparison, aging WT mice gradually lost glucose tolerance and insulin sensitivity and developed hypertension. The gut barrier, compromised in aging WT mice, was preserved in CgA KO mice leading to major 35-fold protection against bacterial DNA-induced inflammation. Similarly, RNA sequencing showed increased expression of the Vsig4 gene (which removes bacterial DNA) in the liver of 2-yr-old CgA-KO mice, which may account for the very low accumulation of microbial DNA in the heart. The reversal of hypertension in aging CgA-KO mice likely stems from (i) low accumulation of microbial DNA, (ii) decreased spillover of norepinephrine in the heart and kidneys, and (iii) reduced inflammation. Conclusion: We conclude that healthy aging relies from protection from bacterial DNA and the consequent low inflammation afforded by CgA-KO. Vsig4 also plays a crucial role in “healthy aging” by counteracting age-associated insulin resistance and hypertension.